Atmosphere, weather, and climate - Barry, Roger G. (Roger Graham), 1935- (Routledge, 2003)
A comprehensive introduction to weather processes and climatic conditions around the world, observed changes and projected future trends: an updated edition, invaluable to all students of the earth's atmosphere and world climate.